A McAb-Based Direct Competitive ELISA to Detect O:9 Salmonella Infection in Chicken - Xia, Zemiao; Geng, Haopeng; Cai, Yuan; Wang, Yaonan; Sun, Daquan; Zhang, Jian; Pan, Zhiming; Jiao, Xin'an; Geng, Shizhong (Frontiers in Veterinary Science, 2020)
Salmonella enteritidis and Salmonella pullorum belonging to Group O9 Salmonella are major causative agents of infectious diseases in chicken. O9 antigen as a part of lipopolysaccharide (LPS) that is a predominant detected target for Salmonella infection. To identify their infection, an anti-O9 monoclonal antibody (McAb)-based direct competitive enzyme-linked assay (O9 Dc-ELISA) was developed after constraints were optimized, the establishment and application of O9 Dc-ELISA, compared to three commercial kits and plate agglutination test (PAT), showed that this O9 Dc-ELISA had better performances than PAT method and commercial kits in sensitivity in addition to strong specificity in the detection of clinical samples.